Spuścizna Stefana Balickiego w zbiorach Domu Literatury Biblioteki Raczyńskich - Przybyszewska, Alicja (Biblioteka Uniwersytecka w Poznaniu, 2015)
Celem artykułu jest prezentacja spuścizny Stefana Balickiego (1899-1939) oraz perspektyw badawczych, jakie otwierają materiały źródłowe tworzące zbiór. Archiwalia literackie i biograficzne dokumentujące życie i twórczą aktywność poznańskiego pisarza i pedagoga pochodzą z rodzinnych zbiorów autora Chłopców, które zostały przekazane Bibliotece Raczyńskich w 2003 roku. W spuściźnie Balickiego szczególne miejsce zajmują rękopiśmienne bruliony z wierszami i dzienniki, prowadzone w latach szkolnych oraz w okresie działań wojennych, przed osiedleniem się pisarza w Poznaniu. Archiwalia te stanowią zarazem ważny przyczynek do badań nad początkami twórczości Balickiego, naznaczonej intensywną pracą poetycką, którą pisarz niemal zupełnie porzucił w okresie dojrzałej aktywności literackiej. Bruliony zawierają autografy kilkuset tekstów poetyckich powstałych w latach 1916-1922, w ogromnej większości nieopublikowanych. Ważnym dokumentem pracy zawodowej są nadto dzienniki prowadzone przez Balickiego – pedagoga, nauczyciela poznańskiego Prywatnego Gimnazjum Humanistycznego im. A. Mickiewicza. Spuścizna, do tej pory w niewielkim stopniu dostępna badaczom biografii i twórczości Balickiego, jest też ważnym dopełnieniem archiwaliów dotyczących pisarza, zgromadzonych w innych polskich bibliotekach i ośrodkach dokumentacyjnych.

This article discusses the literary and critical output of Stefan Balicki (1899-1939) as well as rich research perspectives offered by examining the source materials available in the collection. Literary and biographical archival materials that document the life and artistic work of the Poznań-based writer and educationalist come from the family archives that were handed over to the Raczyński Municipal Public Library in 2003. Hand-written notebooks with his own poems and diaries kept in his school years and then during the war, but before Balicki settled down in Poznań, have a particular place in Balicki’s literary and cultural legacy. Collectively, the archival materials constitute a disparate yet fascinating corpus of biographical, literary and critical fragments, and at the same time are an important contribution to investigations into the beginnings of literary works of Balicki, especially those that were charactersied by intense poetic endeavors soon to be almost completely abandoned by the writer in his mature years of literary activity. The notebooks include autographs of a couple of hundreds of poetic texts, largely unpublished, that originated between 1916 and 1922. Another important documents in Balicki’s professional work are his diaries kept by the Balicki-educationalist and teacher of the private A. Mickiewicz Gymnasium in Poznań. These materials, still awaiting to be properly scientifically addressed by biographers and researchers, are a valuable complement to the archival material concerning the writer currently available in other libraries and documentation centers in Poland.
The literary output of Stefan Balicki in the collection of the Dom Literatury at the Raczyński Municipal Library
Keywords: Stefan Balicki; archiwum literackie; literary archives; literatura poznańska dwudziestolecia międzywojennego; literature in Poznań in the inter-war period; Biblioteka Raczyńskich; Raczyński Municipal Library